AN EXPERIMENTAL COOPERATIVE LEARNING MODEL THINK TALK WRITE (TTW) AND NUMBERED HEADS TOGETHER (NHT) ON THE TOPIC OF FUNCTION IN JUNIOR HIGH SCHOOL SURAKARTA - Lina Utami; Budiyono Budiyono; Riyadi Riyadi (Proceedings Education and Language International Conference, 2017)
The purpose of this research is to determine which one gives better mathematics achievement, students who are taught by learning cooperative model Think Talk Write (TTW), Numbered Heads Together (NHT) or Direct learning model in the topic of Function.The kind of this research is  a quasi-quantitative experimental method. The population is the eighth grade of junior high school students at Surakarta in academic year of 2016/ 2017. The sampling technique were used stratifield cluster random sampling. The data collecting used documentation method and achievement test. The try out of test included difficulty level, discrimination index and reliability index. The data was analyzed using a one-way analysis of variance with unbalanced cells following the normality test with Liliefors method and homogeneity test with Barlett method. Both experimental and control classes should have equal earlier mathematics achievement. Based on result of the research, it can be concluded that students who are taught by TTW and NHT have better mathematics achievement than Direct learning but students who are taught by TTW have equal mathematics achievement with NHT. Keywords : Cooperative, TTW, NHT.